House of quality-based analysis of new service development using context free grammar evaluation-enhanced fuzzy hybrid modelling - Dinçer, Hasan; Yüksel, Serhat; Martinez, Luis (IEEE - Institute of Electrical and Electronics Engineers, Inc, 2021)
The purpose of this study is to analyze new service development competencies based on house of quality (HoQ) in the healthcare industry by using a hybrid interval-valued intuitionistic decision-making approach with fuzzy linguistic information modelled by hesitant fuzzy linguistic term sets (HFLTSs) and linguistic 2-tuples. The novelty of the manuscript is to identify a list of criteria, dimensions, and alternatives for HoQ-based new service development used for the investment decisions in healthcare industry. Thus, a hybrid model with HFLTSs has been proposed, considering 2-tuple linguistic information, Interval-Valued Intuitionistic Fuzzy Sets (IVIFSs) and a defuzzification process with an attitudinal expected score function. Hence, a DEMATEL extension dealing with HFLTSs, linguistic 2-tuple and IVIFS has been developed and used to weigh the criteria and dimensions of customer needs. Similarly, a TOPSIS extension dealing with the same type of information is introduced and applied in order to rank the technical requirements, the so- called "new service development competencies in healthcare industry". Thus, this study contributes to the literature of health economics and management by proposing an original methodology. It is identified that financial expectations play the most significant role for demanders of healthcare services. Hence, competitive pricing strategies should be generated to obtain consumer loyalty in the healthcare industry. Moreover, technological infrastructure is found as the best ranked technical requirement of new service development competencies.
Keywords: Hesitant Fuzzy Linguistic Term Sets; Linguistic 2-Tuples; Interval-Valued Intuitionistic Fuzzy Sets; DEMATEL; New Service Development; Healthcare Industry